The Identity Construction of Solo's Adolescent regarding 'Narimo Ing Pandum' - Rini Darmastuti; Berta Esti Ari Prasetya; T Arie Setyawan P (Jurnal Aspikom, 2020)
Indonesia is a country that is well-know of its diverse ethnicities, languages, and local wisdom. The nation's potential, however, has gradually been threatened by globalization. Globalization was deemed responsible for not only the socio-cultural and local wisdom crisis but also the spread of consumptive behavior in society, including among adolescents. "Narimo Ing Pandum" (NIP) is one of the Indonesian local wisdom that is useful to minimize the problem. However, it has started to be abandoned, including in Solo and Yogyakarta, as the cities of Javanese cultural centers. This paper attempted to construct the identity of Solonese adolescents within NIP. A qualitative research method and an ethnographic approach were used. The research found 1) how the adolescent defined the characteristic of self with NIP, and 2) that NIP is an active deed of the person. The details of the results are discussed further in the paper.